PERTANGGUNGJAWABAN BANK SYARI’AH ATAS KEHILANGAN DANA NASABAH PERSPEKTIF PERATURAN OTORITAS JASA KEUANGAN - Nasution, Nisrina Thufailah; Zulham, Zulham (Legal Standing : Jurnal Ilmu Hukum, 2024)
Islamic banks play a vital role in Indonesia's financial system, especially among Muslims seeking to avoid interest. Loss of customer funds poses a serious issue requiring attention. OJK regulations play a key role in guiding Islamic banks to control the risk of customer fund loss. This research aims to provide an understanding of the roles of banks, OJK, and regulatory implications on the sustainability of Indonesia's Islamic banking sector. This normative study examines the regulatory framework of Islamic banks regarding customer fund loss. The approach includes analysis of legal literature, laws, and OJK case studies. Data collection methods involve literature review and document analysis. The results offer insights into the responsibility of Islamic banks in addressing customer fund loss issues, considering OJK regulations. Islamic banks are accountable for customer fund loss under Financial Services Authority Regulation No. 24/POJK.03/2015. This regulation requires OJK approval to ensure customer fund protection, emphasizing the need for careful supervision to ensure Islamic banks' compliance with established procedures and standards. As the regulator of the financial sector, OJK plays a crucial role in overseeing Islamic banks, ensuring their health and stability, and protecting customers by regulating licensing, overseeing operations, and imposing sanctions when necessary. In addressing customer fund loss in Islamic banks, the Financial Services Authority (OJK) plays a crucial role. OJK regulates, supervises, and enforces Sharia principles while providing protection to customers. Routine inspections by OJK prevent risks and ensure the stability of the Islamic banking sector. OJK can enhance regulations and educate the public to protect customers, reduce the risk of fund loss, and support the growth of Islamic banking.